Folic Acid-Targeted Liposome-Based Nanoparticle Loaded with Sorafenib for Liver Cancer Therapy - Liu S; Yi D; Ma R; Zhang W (International Journal of Nanomedicine)
Songyang Liu,1 Dan Yi,1,2 Rui Ma,1 Wei Zhang1 1Department of Hepatobiliary and Pancreatic Surgery, General Surgery Center, The First Hospital of Jilin University, Changchun, 130061, People’s Republic of China; 2Department of VascularSurgery Qiqihar first hospital, Qiqihar City, Heilongjiang Province, 161000, People’s Republic of ChinaCorrespondence: Wei Zhang, Department of Hepatobiliary and Pancreatic Surgery, General Surgery Center, The First Hospital of Jilin University, 1 Xinmin Street, Changchun, 130061, People’s Republic of China, Email zhangwei0312@jlu.edu.cnIntroduction: Sorafenib (SF) is a small molecule involved in tumor proliferation and angiogenesis. SF is inhibitor of several kinases, including RAF, VEGFR, and PDGFR. However the weak targeting ability of SF for liver tumor tissues is the major problem in clinical therapy. Therefore, a SF-loaded folic acid-targeted liposome drug delivery system was devised for targeting liver tumor therapy in this study.Methods: Folic acid (FA), HSPC, DSPE-PEG2k, CHO, and SF were composed to prepare a folic acid-targeted SF-loaded liposome (LSF) drug delivery system. LSF and drug loading content was established through thin-film-hydration technique and HPLC, respectively. The particle size and stability of LSF were examined by dynamic light scattering (DLS). The inhibition effect of LSF was elucidated in vitro on liver cancer cells through cell cytotoxicity and apoptosis experiments. The tumor-inhibiting efficacy was measured on liver xenograft model.Results: The drug loading content (DLC) of LSF was 3.6%. The diameter of LSF was 197.1± 16.6 nm, and LSF was stable during 24 h. Liver cancer cells could be effectively inhibited by LSF in vitro. LSF could substantially induce apoptosis. Also, LSF could inhibit tumor growth effectively in vivo. LSF could reduce side effects of SF demonstrated by bio-safety tests.Conclusion: LSF is a FA-targeted drug delivery system that could effectively inhibit the progression of liver cancer.Keywords: folic acid, liver cancer, liposome, sorafenib, targeting delivery